2021
DOI: 10.1038/s41408-021-00468-6
|View full text |Cite|
|
Sign up to set email alerts
|

Germline variants at SOHLH2 influence multiple myeloma risk

Abstract: Multiple myeloma (MM) is caused by the uncontrolled, clonal expansion of plasma cells. While there is epidemiological evidence for inherited susceptibility, the molecular basis remains incompletely understood. We report a genome-wide association study totalling 5,320 cases and 422,289 controls from four Nordic populations, and find a novel MM risk variant at SOHLH2 at 13q13.3 (risk allele frequency = 3.5%; odds ratio = 1.38; P = 2.2 × 10−14). This gene encodes a transcription factor involved in gametogenesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Prior whole exome sequencing (WES) studies in MM have identified potential rare germline variants in DIS3 [2] and LSD1/KDM1A [3] and also pointed out potential risk variants in ARID1A, USP45 [4], EP300 [5], DCHS1 , and KIF1B [6]. Additionally, genome‐wide association studies (GWAS) have recognized 25 different MM risk loci [7]. Our aim was to determine the frequency of rare pathogenic (P) or likely pathogenic (LP) germline variants and to discover novel genes linked to the MM predisposition in Finnish patients taking an advantage of the large population‐specific control set gnomAD noncancer Finns.…”
Section: Short Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior whole exome sequencing (WES) studies in MM have identified potential rare germline variants in DIS3 [2] and LSD1/KDM1A [3] and also pointed out potential risk variants in ARID1A, USP45 [4], EP300 [5], DCHS1 , and KIF1B [6]. Additionally, genome‐wide association studies (GWAS) have recognized 25 different MM risk loci [7]. Our aim was to determine the frequency of rare pathogenic (P) or likely pathogenic (LP) germline variants and to discover novel genes linked to the MM predisposition in Finnish patients taking an advantage of the large population‐specific control set gnomAD noncancer Finns.…”
Section: Short Reportmentioning
confidence: 99%
“…DCHS1, and KIF1B [6]. Additionally, genome-wide association studies (GWAS) have recognized 25 different MM risk loci [7]. Our aim was to determine the frequency of rare pathogenic (P) or likely pathogenic (LP) germline variants and to discover novel genes linked to the MM predisposition in Finnish patients taking an advantage of the large population-specific control set gnomAD noncancer Finns.…”
mentioning
confidence: 99%
“…Several studies have investigated the genetic susceptibility of MM, using genome‐wide association studies (GWAS) 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 or more targeted approaches. 8 , 11 , 12 , 13 , 14 , 15 Twenty‐four risk loci have been found to be associated with MM risk through GWAS; however, these variants explain approximately only 16% of MM heritability.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a large portion of missing heritability to be identified. Previous genome-wide association studies (GWAS) have successfully identified 24 common loci associated with MM risk [ 3 , 4 ]; of these, 12 are also associated with MGUS [ 5 ]. Twenty additional loci have been identified for risk of MGUS but the impact of these loci on progression is unknown [ 5 , 6 ].…”
mentioning
confidence: 99%
“…However, 33% of MGUS cases from Mayo Clinic were identified via screening alone; sensitivity analysis excluding MGUS identified by screening were performed. Genotyping, imputation, population stratification, principal components analysis, and related quality control steps were performed according to established standards (genotype call rate >90% and imputation quality >0.6) [ 4 , 6 ]. Common single nucleotide polymorphisms (SNPs) with minor allele frequency (MAF) > 0.01 within each GWAS were analyzed using SNPTEST or PLINK v1.9.…”
mentioning
confidence: 99%